(untitled) (Biological Sciences - PJSIR, 2002)
Six plant communities viz., Themeda-Dodonaea-Maytenus, Dodonaea-Maytenus, Phoenix- Cyn odon-i\1icromeria, Dodonaea-Otostegia-Themeda, Dodonaea-Th emeda-Mallotus, Pinus-Hypod ematium-Dodonaea were established on the basis of phytosociological attributes on sunside at Mai Dhani Hill, Muzaffarabad in December , 1995. The highest species diversity is shown by Phoenix-Cynodon-Micromeria communi ty at 970 m elevation while the lowest species diversity i s shown by Dodonaea-Otostegia-Themeda community at 980 m elevation. With the increase of an altitude the species diversity decreased. The study area has sandy loam to loam type soil. The pH of the soil in the study area was slightly alkaline in nature. Organic matter varies from 2 .0 to 2.65%. The CaC0 content varies from 1 5.7 to 23.2% while total 3 soluble salts vary from 0.022 to 0.58%. There was a decrease in soil temperatu re from lower to higher altitudes.